Sistem Pemetaan Lokasi Ruang Kelas di Kampus A Universitas Dirgantara Marsekal Suryadarma - Thalbiyatul Ilmiyah; Yohannes Dewanto (JURNAL TEKNOLOGI INDUSTRI, 2026)
The use of information technology in higher education plays an important role in providing fast and easily accessible information services. One common problem is the difficulty in finding classroom locations and accessing course schedule information efficiently. Conventional information media are considered less interactive and less effective in addressing these needs. This study aims to design and implement a touchscreen based system for classroom location mapping and student course schedules at Campus A of Universitas Dirgantara Marsekal Suryadarma. The system is developed as a standalone desktop application that can operate offline without requiring an internet connection. The system design emphasizes simple navigation and comfortable user interaction on touch-screen devices. The research method includes system design, implementation, and evaluation. System testing consists of functional testing using the Black Box method, response testing by measuring the delay between touch input and visual system response, and usability testing using the System Usability Scale (SUS). The results show that the system demonstrates good responsiveness with delay values ranging from 174 to 249 ms, which are within acceptable limits, and achieves an average SUS score of 82, indicating good usability. Based on these results, it can be concluded that the developed system functions properly, is responsive, and is easy to use as an interactive information medium in the campus environment.